Deuterium retention in mixed Be-W-D codeposited layers. (22nd September 2020) - Zibrov, M.S.; Baldwin, M.J.; Mayer, M.; Nguyen, H.Q.; Brezinsek, S.; Doerner, R.P.
Abstract: Mixed beryllium-tungsten-deuterium (Be-W-D) layers (4.4–28.4 at.% W) were codeposited in a magnetron discharge in D2 -Ar atmosphere at pressures of 0.8 Pa, 2.7 Pa, and 8 Pa and a substrate temperature of 373 ± 15 K. The composition of the layers was determined using nuclear reaction analysis and Rutherford backscattering spectrometry. D trapping states in the layers were examined using thermal desorption spectroscopy. At all pressures used, the D concentration in the layers has a non-monotonic dependence on the W concentration, with the maximum occurring at 4.4–7.3% W. In this case, the D concentration is about two times greater than that in a Be-D layer; in W-D layers the D concentration is more than one order of magnitude smaller. Increase of pressure during deposition results in an increase of the D concentration in Be-D and Be-W-D (4.4–7.3% W) layers and is linked with the appearance of sharp low-temperature D release peaks near 450 K and 500 K. Increase of pressure also results in steeper decrease of the D concentration with increasing W concentration beyond 7.3%. It is concluded that for the layers deposited at 450 K and above, the effect of the presence of W (4.4–28.4%) on the D retention becomes small.